PENGARUH BUDAYA TRI HITA KARANA, AKUNTABILITAS, GAYA KEPEMIMPINAN, DAN PENGAWASAN INTERNAL TERHADAP KINERJA KARYAWAN PADA LEMBAGA PERKREDITAN DESA (LPD) DI KECAMATAN NUSA PENIDA - Ni Luh Devi Srikasih; Ni Komang Sumadi; Putu Cita Ayu (UNHI Press, 2022)
Employee performance affects the success of a company, including financial institutions, both bank and non-bank financial institutions such as the Village Credit Institution (LPD). The purpose of this study was to determine the influence of Tri Hita Karana Culture, Accountability, Leadership Style and Internal Control on the Performance of Village Credit Institutions (LPD). This research was conducted at the Village Credit Institution (LPD) Nusa Penida District. This research was conducted in 45 Village Credit Institutions (LPD) located in Nusa Penida District with a population of 180 people. The sampling method used is a non-probability sampling method with a purposive sampling technique based on certain considerations. The total sample taken is 150 people who are directly related to the performance of the Village Credit Institution (LPD), namely the LPD chairman, secretary, treasurer and employees who work more than 1 year. The data analysis technique used is Multiple Linear Regression. The results of this study indicate that the Tri Hita Karana Culture, Accountability, Leadership Style and Internal Control have a positive